2019
DOI: 10.26710/jafee.v5i2.938
|View full text |Cite
|
Sign up to set email alerts
|

Does CSR Enhance Young Bank Customers’ Satisfaction and Loyalty in a Developing Economy? The Mediating Role of Trust

Abstract: The role of corporate social responsibility (CSR) on firm performance is well documented in the literature. Although the majority of the evidence available points to a positive association between CSR and determinants of company performance such as monetary performance, personnel commitment and corporate identity, findings still remain rather inconclusive as negative or no correlation results are also reported. In addition, little is known about how CSR is perceived from a bank customer’s point of view and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Likewise, customers who feel satisfied with services provided by banks are more likely to repeat the transactions and work as advertising for the firm by recommending it to more people [34,46]. Other investigations indicated that CSR activities from banks indeed affect customer satisfaction and loyalty [47,48]. The accomplishment of consumers' expectations and necessities increases their loyalty.…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%
“…Likewise, customers who feel satisfied with services provided by banks are more likely to repeat the transactions and work as advertising for the firm by recommending it to more people [34,46]. Other investigations indicated that CSR activities from banks indeed affect customer satisfaction and loyalty [47,48]. The accomplishment of consumers' expectations and necessities increases their loyalty.…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%
“…In the process of evaluating and analyzing the default risk of bank customers, strengthen the implementation of "three inspections," reformulate the punishment mechanism, and strictly implement the new punishment mechanism, so as to not only take credit performance as the reward standard [21,22]. In terms of short-term economic development, high-risk and high interest bank credit will indeed produce good profit space, but in the long run, the default risk of bank customers is increasing, which is not conducive to long-term stable development.…”
Section: Strengthen the Implementation Of " Ree Checks" In The Mathem...mentioning
confidence: 99%
“…For instance, prior literature has documented that socially responsible firms have lower equity capital costs (Dhaliwal et al, 2011, 2012; Torugsa et al, 2013), enhanced profitability (Kumar et al, 2016), good corporate reputation (Ozdora‐Aksak et al, 2016) and risk profile (Cui et al, 2018), receive more recommendations from analysts (Ioannou & Serafeim, 2015) and better reactions from investors, particularly in controversial industries (Christensen, 2016; Lackmann et al, 2012). Moreover, social responsibility activities will increase stakeholders' (e.g., investors) perception of trust in the organisation as well as their financial information (Kim et al, 2012), which then results in better organisational performance, such as larger market share, higher customer satisfaction and greater profit creation (see Brammer & Millington, 2008; Carmeli et al, 2007; Kim et al, 2012; Zulu‐Chisanga, 2019). Even during the financial crisis of 2008, a firm's CSR efforts have also been confirmed to help them successfully re‐establish trust between themselves and their investors (Giannarakis & Theotokas, 2011).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%